Assessing the influence of scanner background noise on auditory processing. I. An fMRI study comparing three experimental designs with varying degrees of scanner noise - Gaab, Nadine; Gabrieli, John D.E.; Glover, Gary H. (Human brain mapping, 2007)
We compared two experimental designs aimed at minimizing the influence of scanner background noise (SBN) on functional MRI (fMRI) of auditory processes with one conventional fMRI design. Ten subjects listened to a series of four one‐syllable words and had to decide whether two of the words were identical. This was contrasted with a no‐stimulus control condition. All three experimental designs had a duration of ∼17 min: 1) a behavior interleaved gradients (BIG; Eden et al. [1999] J Magn Reson Imaging 41:13–20) design (repetition time, TR, = 6 s), where stimuli were presented during the SBN‐free periods between clustered volume acquisitions (CVA); 2) a sparse temporal sampling technique (STsamp; e.g., Gaab et al., [2003] Neuroimage 19:1417–1426) acquiring only one set of slices following each of the stimulations with a 16‐s TR and jittered delay times between stimulus offset and image acquisition; and 3) an event‐related design with continuous scanning (ERcont) using the stimulation design of STsamp but with a 2‐s TR. The results demonstrated increased signal within Heschl's gyrus for the STsamp and BIG‐CVA design in comparison to ERcont as well as differences in the overall functional anatomy among the designs. The possibility to obtain a time course of activation as well as the full recovery of the stimulus‐ and SBN‐induced hemodynamic response function signal and lack of signal suppression from SBN during the STsamp design makes this technique a powerful approach for conducting auditory experiments using fMRI. Practical strengths and limitations of the three auditory acquisition paradigms are discussed. Hum Brain Mapp, 2006. © 2006 Wiley‐Liss, Inc.